Conceptualizing a quality of life framework for girls with Rett syndrome using qualitative methods - Epstein, A.; Leonard, H.; Davis, E.; Williams, K.; Reddihough, D.; Murphy, N.; Whitehouse, A.; Downs, Jennepher (2015)
Rett syndrome is a neurodevelopmental disorder mainly affecting females and associated with a mutation on the MECP2 gene. There has been no systematic evaluation of the domains of quality of life (QOL) in Rett syndrome. The aims of this study were to explore QOL in school-aged children with Rett syndrome and compare domains with those identified in other available QOL scales. The sample comprised 21 families registered with the Australian Rett Syndrome Database whose daughter with Rett syndrome was aged 6-18 years. Semi-structured telephone interviews were conducted with each parent caregiver (19 mothers, 2 fathers) to investigate aspects of their daughter's life that were satisfying or challenging to her. Qualitative thematic analysis using a grounded theory framework was conducted, and emerging domains compared with those in two generic and three disability parent-report child QOL measures. Ten domains were identified: physical health, body pain, and discomfort, behavioral and emotional well-being, communication skills, movement and mobility, social connectedness, variety of activities, provision of targeted services, stability of daily routines, and the natural environment. The two latter domains were newly identified and each domain contained elements not represented in the comparison measures. Our data articulated important aspects of life beyond the genetic diagnosis. Existing QOL scales for children in the general population or with other disabilities did not capture the QOL of children with Rett syndrome. Our findings support the construction of a new parent-report measure to enable measurement of QOL in this group. © 2015 Wiley Periodicals, Inc.